Intrathecal Drug Delivery Systems for the Management of Chronic Noncancer Pain: A Systematic Review of Economic Evaluations. Issue 5 (1st December 2017) - Duarte, Rui V.; Lambe, Tosin; Raphael, Jon H.; Eldabe, Sam; Andronis, Lazaros
Abstract: Background: Intrathecal drug delivery (ITDD) systems are one of a limited number of management options for chronic noncancer pain, cancer pain, and spasticity. Concerns over their effectiveness and high initial costs led National Health Service (NHS) England to decommission ITDD for patients with chronic noncancer pain. However, the extent to which this decision is in line with existing economic evidence is unclear. The aim of this systematic review was to identify and review the existing evidence on the cost effectiveness of ITDD for chronic noncancer pain. Methods: Full and partial economic evaluations on ITDD were identified through systematic searches in MEDLINE, Embase, Web of Science, and the NHS for Reviews and Dissemination databases. Database searches were complemented by hand searching of reference lists of relevant studies and searches of grey literature. Study selection was carried out by 2 assessors, independently. Study quality assessment was performed to inform critical appraisal of health economics studies. Data were extracted using a data extraction form developed for the purposes of this study. Results: Four thousand four hundred and sixty‐four unique studies were identified, of which 7 met the inclusion criteria. With the exception of 1 study, the studies found ITDD to be either cost saving or cost effective compared to conventional medical management. ITDD became cost ineffective in 1 further study following price year adjustment to 2016. Conclusions: Study findings showed ITDD to be not cost effective only in extremely conservative scenarios. There is limited evidence on the effectiveness of ITDD in noncancer pain; however, the available economic evidence controverts arguments to refute the treatment on economic grounds.